THE OCCURRENCE OF JELLYFISH IN COASTAL WATERS OF MAKASSAR, SOUTH SULAWESI, INDONESIA - Fitriani, Fitriani; Tambaru, Rahmadi; Rasyid , Abd; Yusuf, Syafyudin (Hasanuddin University, 2020)
Jellyfish can be found in most coastal waters and their occurrence can be frequent during the day. This study aimed to detect the occurrence of jellyfish based on the oceanographic condition in the coastal waters of Makassar. Observations were conducted in July-September 2018 at three stations namely Port of Soekarno Hatta (Station 1), Port of Paotere (Station 2), and Port of Untia (Station 3). Jellyfish sampling was conducted in the morning, noon and afternoon, from three stations as aforementioned. Jellyfish samples were taken and identified at the Laboratory of Marine Biology, Faculty of Marine Science and Fisheries, Universitas Hasanuddin. Oceanographic conditions, i.e. temperature, salinity, transparency, and current velocity, were measured. All data were analyzed descriptively. It showed that the oceanographical conditions were in the suitable range for supporting jellyfish growth. Three genera of jellyfish were found, namely Aurelia, Porpita, and Aequorea. Aurelia was abundant in Station 1 and 2, whereas Porpita in Station 3. It also showed that during the afternoon, the jellyfish occurred more frequently.